The role of TMPRSS2:ERG in molecular stratification of PCa and its association with tumor aggressiveness: a study in Brazilian patients - Eguchi, Flavia C.; Faria, Eliney F.; Scapulatempo Neto, Cristovam; Longatto-Filho, Adhemar; Zanardo-Oliveira, Cleyton; Taboga, Sebastiao R. [UNESP]; Campos, Silvana G. P. [UNESP] (Nature Publishing Group, 2014)
Recurrent gene fusions between the genes TMPRSS2 and ERG have been described in prostate cancer (PCa) and are found in 27% to 79% of radical prostatectomy. This fusion transcription results in ERG overexpression, which can be detected by immunohistochemistry (IHC) and provide a potential diagnostic marker for PCa. Three tissue microarrays (TMAs) containing samples from 98 patients with PCa and one TMA of 27 samples from individuals without PCa were tested for ERG immunostaining, and the presence of TMPRSS2: ERG transcripts was confirmed by quantitative real time PCR (qRT-PCR). The results showed that 46.9% of tumors tested positive for ERG immunostaining, and this finding was consistent with the results of qRT-PCR testing (k = 0.694, p < 0.001). IHC had a specificity of 83.3% and a sensitivity of 81% in detecting TMPRSS2:ERG fusion. Patients with PSA < 4.0 ng/mL showed positive immunoreactivity for ERG (p = 0.031). Kaplan-Meier analysis suggested that ERG expression did not influence the time of biochemical recurrence. This study demonstrates that both IHC and qRT-PCR are useful tools in detecting TMPRSS2: ERG fusions. A correlation between ERG expression and clinical and pathological parameters was not found, but the frequency, specificity and recurrence of ERG in PCa suggests that it may be a potential adjunct diagnostic tool.
Keywords: DIAGNOSTIC MARKERS; BIOMARKERS